Perkawinan Beda Agama dalam Penafsiran Muhammad Rasyid Ridha dan Hamka - Hasiah Hasiah; Sawaluddin Siregar (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
As for the background of this research, it is known that the issue of interfaith marriage has become a polemic and even relevant issue to be studied. This issue continues to be discussed by scholars because interfaith marriages are still common in socienty. Muhammad Rasyid Ridha and Hamka as mufassir where this social problem also occurs at a time when they feel responsible for finding legal solutions in the Qur’an to the problem of interfaith marriages that occur among these people. The results obtained from this study are: first, related to marriage between Muslim men and Muslim women. Their interpretation of the verse is that it is unlawful for a muslim man to marry a muslim women. However, according to Muhammad Rasyid Ridha, the word polytheist in the verse is of a special form, namely only Arab polytheists. While according to Hamka the polytheists in general. Second, releated to marriage between Muslim men and women of the peiple of the book. Their interpretation of the verse is that it is permissible for a Muslim man to marry a women of the people of the book. According to Muhammad Rasyid Ridha, the criteria of the scribes are as long as they have a holy book. Meanwhile, according to Hamka, the people of the book are only limited to Jews and Christians.